Analysis of Eating Patterns and Parity with the Incidence of Chronic Energy Deficiency in Pregnant Women: Literature Review - Puspitasari, Vindi; Qotijah, Rahayu Siti; Qamaria, Aziza Ainur (Griya Eka Sejahtera, 2023)
Background: The high incidence of Chronic Energy Deficiency (CED) in pregnant women in Indonesia can result in risks and complications for pregnant women and their unborn children. The high parity of pregnant women causes the condition of the reproductive organs to become weaker, which has an impact on the health of the mother and baby. In addition, the poor diet of pregnant women causes inadequate nutritional intake during pregnancy, which causes CED. Methods: Method this research is literature review, which sourced from Google Scholar and PubMed databases published from 2016 to 2020, and manually selected articles relevant to the research questions. Results: The research results show that Parity and diet do not have a direct effect, but are risk factors that can cause CED in pregnant women, so all efforts to prevent CED must always pay attention and be alert to mothers with parity and eating patterns that are at risk.Conclusion: It is hoped that there will be efforts to increase knowledge of information regarding reproductive health and nutrition of pregnant women so that a woman can better prepare for her pregnancy process and the need to take precautions if she has risk factors for CED